Lightning interference in multiple antennas wireless communication systems - Ahmad, Mohd Riduan; Mohd Esa, Mona Riza; Rahman, Mahbubur; Cooray, Vernon; Dutkiewicz, Eryk (Bentham Open, 2012)
This paper analyzes the interference of lightning flashes with multiple antennas wireless communication systems operating in the microwave band at 2.4 GHz and 5.2 GHz. A bit error rate (BER) measurement method was used to evaluate BER and packet error rate (PER) during 5 heavy thunderstorms on January 25 and March 17 to 20, 2011, respectively. In addition, BER measurements also were done on January 21 and March 30, 2011 under fair weather (FW) conditions providing a baseline for comparison. The Transmitter-Receiver separation was fixed at 10 meter with line-of- sight (LOS) consideration. We infer that lightning interfered with the transmitted digital pulses which resulted in a higher recorded BER. The maximum recorded BER was 9.9·10-1 and the average recorded BER and PER were 2.07·10-2 and 2.44·10-2 respectively during the thunderstorms with the average fair weather BER and PER values under the influence of adjacent channel interference (ACI) and co-channel interference (CCI) being 1.75·10-5 and 7.35·10-6 respectively. We conclude that multiple antennas wireless communication systems operating at the microwave frequency can be significantly interfered by lightning.